О НЕКОТОРЫХ ЭЛЕМЕНТАХ СИСТЕМЫ ПОДГОТОВИТЕЛЬНЫХ И РЕЧЕВЫХ УПРАЖНЕНИЙ ПО ФОРМИРОВАНИЮ НАВЫКОВ ДИАЛОГИЧЕСКОГО ОБЩЕНИЯ УЧАЩИХСЯ ГИМНАЗИЧЕСКОГО ЗВЕНА В РЕГИОНЕ С КОМПАКТНЫМ ПРОЖИВАНИЕМ ГАГАУЗОВ - Надежда КОЧАНЖИ (Moldova State University, 2020)
În articol este abordată formarea competenței comunicative a elevilor la lecțiile de limbă și literatură găgăuză, prin dezvoltarea abilităților de vorbire dialogică. Sunt prezentate exerciții pregătitoare și de vorbire care contribuie la formarea competenței comunicative a elevilor de la gimnaziu, fiind furnizate informații despre elementele sistemului de exercițiu pentru dezvoltarea unui discurs dialogal care ar trebui să vizeze formarea competențelor specifice limbii găgăuze. Este de remarcat rolul important pe care îl are învățarea de a formula replici şi întrebări în actul de comunicare dialogală. ON SOME ELEMENTS OF THE PREPARATORY AND SPEECH EXERCISES FOR DIALOGICAL COMMUNICATION SKILLS DEVELOPMENT IN GYMNASIUM STUDENTS FROM A REGION DENSLY INHABITED BY THE GAGAUZ PEOPLE The article discusses the formation of students' communicative competence during the classes of "the Gagauz language and literature", through the development of dialogical speech skills. The article presents preparatory and speech exercises that contribute to the formation of communicative competence of gymnasium students. Information is given about the elements of the exercise system for the development of dialogical speech, which should be aimed at forming the designated specific competences in the Gagauz language, that is, at teaching students not only questions and answers, but also at compiling response statements, exchanging opinions, and picking up the interlocutor's thoughts. The important role of teaching students how to formulate replies, questions, and use speech cliches is highlighted.